Beyond the K-valley: exploring unique trion states in indirect band gap monolayer WSe2 - Carl Emil Mørch Nielsen; Franz Fischer; Gabriel Bester (npj 2D Materials and Applications)
Abstract We calculate the optical properties of monolayer WSe2 using ab initio many-body screened configuration interaction. For this indirect band gap material we describe additional species of negatively charged trions involving the Q-valley which are energetically more favorable than those formed at the K-valley. While the results are in excellent agreement with experimental data, they shed new light on observed but yet unaddressed optical features. The analysis of the many-body interactions reveals mechanisms behind increased singlet-triplet splitting and redshifted energies in these Q-valley trions, compared to K-valley trions.